Evaluación del biogás como energía alternativa generado en las chimeneas del relleno sanitario "La Esmeralda" en Manizales, Caldas (2019)
In the present work of degree wants to evaluate the biogas that is produced in the chimneys of the sanitary landfill of Manizales "La Esmeralda" to determine the viability of this as an alternative energy source thanks to the natural process by decomposition of urban solid waste, the company EMAS SAS, who sees an opportunity to use this resource as a possible source of alternative energy, also sees that through a process of purification and use it contributes to the mitigation of the environmental impact that occurs when this gas is released into the atmosphere and have negative effects on the environment, since this biogas is considered a greenhouse gas.